Activity of botulinum toxin type A in cranial dura: implications for treatment of migraine and other headaches. (19th December 2015) - Lacković, Zdravko; Filipović, Boris; Matak, Ivica; Helyes, Zsuzsanna
Abstract : Background and Purpose: Although botulinum toxin type A (BoNT/A) is approved for chronic migraine treatment, its mechanism of action is still unknown. Dural neurogenic inflammation (DNI) commonly used to investigate migraine pathophysiology can be evoked by trigeminal pain. Here, we investigated the reactivity of cranial dura to trigeminal pain and the mechanism of BoNT/A action on DNI. Experimental Approach: Because temporomandibular disorders are highly comorbid with migraine, we employed a rat model of inflammation induced by complete Freund's adjuvant, followed by treatment with BoNT/A injections or sumatriptan p.o. DNI was assessed by Evans blue‐plasma protein extravasation, cell histology and RIA for CGRP. BoNT/A enzymatic activity in dura was assessed by immunohistochemistry for cleaved synaptosomal‐associated protein 25 (SNAP‐25). Key Results: BoNT/A and sumatriptan reduced the mechanical allodynia and DNI, evoked by complete Freund's adjuvant. BoNT/A prevented inflammatory cell infiltration and inhibited the increase of CGRP levels in dura. After peripheral application, BoNT/A‐cleaved SNAP‐25 colocalized with CGRP in intracranial dural nerve endings. Injection of the axonal transport blocker colchicine into the trigeminal ganglion prevented the formation of cleaved SNAP‐25 in dura. Conclusions and Implications: Pericranially injected BoNT/A was taken up by local sensory nerve endings, axonally transported to the trigeminal ganglion and transcytosed to dural afferents. Colocalization of cleaved SNAP‐25 and the migraine mediator CGRP in dura suggests that BoNT/A may prevent DNI by suppressing transmission by CGRP. This might explain the effects of BoNT/A in temporomandibular joint inflammation and in migraine and some other headaches.